Exploration of the Potential of Local Cassava Genotypes to Support Food Security in the Highlands of Toba Regency - Setiawan, Andi; Rosmayati, Rosmayati; Rahmawati, Nini (Action Research Literate, 2025)
One of the cassava-producing districts in the highlands topography is Toba Regency. Cassava plantation centres spread across Toba Regency are located in Laguboti District. Cassava land is starting to be displaced due to a lack of land management and processing. This study aims to enable the community to maximize the growth of cassava-based on different genotypes and land use according to soil characteristics so as to increase the production of cassava as a food crop in Toba Regency, North Sumatra, Indonesia. The method is the determination of land units, observations of morphological characteristics of cassava, observations of land characteristics, and the collection and analysis of soil samples on cassava fields carried out in the laboratory. The results were 7 types of cassava diversity in Toba Regency with different morphological characters, namely Malaysia (G1), Siroti (G2), Simerah (G3), Sumedang (G4), Siputih (G5), Adira (G6) and UJ5. (G7). The distribution of pH and nutrient content in each cassava field with different genotypes in Laguboti District, Toba Regency is very varied. pH ranged from acid-neutral, Nitrogen ranged from 0.17% – 0.63%, Phosphorus ranged from 0.05% – 0.24%, and Potassium ranged from 0.04% – 0.27%. The altitude of the place ranges from 920-940 m asl.